The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.jalgebra.2005.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantum- and quasi-Plücker coordinates

Abstract: We demonstrate a passage from the "quasi-Plücker coordinates" of Gelfand and Retakh, to the quantum Plücker coordinates built from q-generic matrices. In the process, we rediscover the defining relations of the quantum Grassmannian of Taft and Towber and provide that algebra with more concrete geometric origins.  2005 Elsevier Inc. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…There is a rich literature on quantum or noncommutative deformations of grassmannians (see e.g. [32,40,23,21,27]), mostly relying on q-deformations of matrices, so our noncommutative relations are somewhat different and easier to deal with. This is because in our construction the minors of a noncommutative matrix still close to a noncommutative algebra and in §2.4 we have explicitly computed their noncommutativity relations; these will be the noncommutativity relations of the homogeneous coordinate algebra generators of the noncommutative projective space CP N Θ .…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a rich literature on quantum or noncommutative deformations of grassmannians (see e.g. [32,40,23,21,27]), mostly relying on q-deformations of matrices, so our noncommutative relations are somewhat different and easier to deal with. This is because in our construction the minors of a noncommutative matrix still close to a noncommutative algebra and in §2.4 we have explicitly computed their noncommutativity relations; these will be the noncommutativity relations of the homogeneous coordinate algebra generators of the noncommutative projective space CP N Θ .…”
Section: 3mentioning
confidence: 99%
“…This is because in our construction the minors of a noncommutative matrix still close to a noncommutative algebra and in §2.4 we have explicitly computed their noncommutativity relations; these will be the noncommutativity relations of the homogeneous coordinate algebra generators of the noncommutative projective space CP N Θ . Here we shall follow [32] to define the noncommutative deformation of Plücker equations, or Young symmetry relations, which is an approach to noncommutative grassmannians based on quasideterminants [23].…”
Section: 3mentioning
confidence: 99%
“…In this subsection, we summarize formulas on quasi-determinants based on [21,22,23] (see also [30,31,32,33]). Let A = (a ij ) 1≤i,j≤N be a N × N matrix whose matrix elements a ij are elements of an associative algebra.…”
Section: Review On Quasi-determinantsmentioning
confidence: 99%
“…The fact that the quantum Yang-Baxter maps are expressed in terms of quasi-Plücker coordinates over matrices (2.144), (2.151) and (2.160) composed of the Loperators may imply an underlying quantum Grassmannian of the system (cf. [32]). It is known that L-operators are related to Manin matrices [30,31].…”
Section: )mentioning
confidence: 99%
“…Perhaps a theory of non-commutative flag varieties using quasi-Plücker coordinates could help explain the choices for the relations in F q (n). In [12], it is shown that any relation (Y I,J ) (a) has a quasi-Plücker coordinate origin. Section 3 shows that (1) Looking past flag algebras to more general determinantal varieties, the same question is valid.…”
Section: G-proof Of Theoremmentioning
confidence: 99%